2011
DOI: 10.4081/rt.2011.e48
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for marginally resected, unresectable or recurrent giant cell tumor of the bone: a rare cancer network study

Abstract: The role of radiotherapy for local control of marginally resected, unresectable, and recurrent giant cell tumors of bone (GCToB) has not been well defined. The number of patients affected by this rare disease is low. We present a series of 58 patients with biopsy proven GCToB who were treated with radiation therapy. A retrospective review of the role of radiotherapy in the treatment of GCToB was conducted in participating institutions of the Rare Cancer Network. Eligibility criteria consisted of the use of rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 10 publications
(16 reference statements)
0
18
0
1
Order By: Relevance
“…The role of primary radiotherapy for the treatment of these tumors is controversial due to earlier reports that GCTs could turn malignant after radiotherapy [Glasscock and Hunt, 1974]. A multiinstitutional study of 58 patients with GCTs treated by radiotherapy in European and North American academic centers by Bhatia et al [2011] reported no malignant transformation in any of the cases. They reported 5-year overall survival of 94% and 5-year disease-free survival of 81%.…”
Section: Surgical Managementmentioning
confidence: 99%
“…The role of primary radiotherapy for the treatment of these tumors is controversial due to earlier reports that GCTs could turn malignant after radiotherapy [Glasscock and Hunt, 1974]. A multiinstitutional study of 58 patients with GCTs treated by radiotherapy in European and North American academic centers by Bhatia et al [2011] reported no malignant transformation in any of the cases. They reported 5-year overall survival of 94% and 5-year disease-free survival of 81%.…”
Section: Surgical Managementmentioning
confidence: 99%
“…To reduce the risk of recurrence, aggressive surgical approaches (joint resection, amputation, hemipelvectomy) are often applied. For unresectable GCTB patients, radiotherapy and serial embolization can relieve the symptoms for a short period, but the duration of effect is limited (13). Moreover, malignant transformation can occur after radiation (14).…”
Section: Introductionmentioning
confidence: 99%
“…This is because it mostly occurred in the epiphysis or metaepiphyseal location with extension to subchondral bone and the most commonly affected region is the knee which was about 50-55 %. 2,5 In this study, the very rare site of GCT of bone even occurs in one patient each, affecting zygoma, mandibular, vertebrae and distal tibia. Besides that, there are only four patients with GCT affecting the rare site, the bones of the feet.…”
Section: Discussionmentioning
confidence: 99%